Challenges in pre-clinical testing of anti-cancer drugs in cell culture and in animal models - HogenEsch, Harm (2012)
Experiments with cultures of human tumor cell lines, xenografts of human tumors into immunodeficient mice, and mouse models of human cancer are important tools in the development and testing of anti-cancer drugs. Tumors are complex structures composed of genetically and phenotypically heterogeneous cancer cells that interact in a reciprocal manner with the stromal microenvironment and the immune system. Modeling the complexity of human cancers in cell culture and in mouse models for preclinical testing is a challenge that has not yet been met although tremendous advances have been made. A combined approach of cell culture and mouse models of human cancer is most likely to predict the efficacy of novel anti-cancer treatments in human clinical trials.